2020
DOI: 10.3389/fphar.2019.01642
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profile and Bioactivities of Sideritis perfoliata L.: The Plant, Its Most Active Extract, and Its Broad Biological Properties

Abstract: Sideritis, also named "ironwort," "mountain tea," or "shepherd's tea," is a genus of flowering plants used as herbal medicine in traditional Mediterranean-area medicine systems, and these plants are generally consumed as a herbal tea. Its use as herbal tea and in traditional herbal medicine is quite popular. There are currently few studies on Sideritis perfoliata L., and only one reports the use of a liquid chromatography coupled to diode array detection and electrospray ionization tandem mass spectrometry (LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…The examined extracts were characterized by quite low or moderate ion chelating ability. It was found that water extract of S. perfoliata had approximately ten times higher activity than the RL aqueous samples [ 51 ]. Similarly, decoctions and infusions made from different Crataegus species were ten times more active than our aqueous extracts [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…The examined extracts were characterized by quite low or moderate ion chelating ability. It was found that water extract of S. perfoliata had approximately ten times higher activity than the RL aqueous samples [ 51 ]. Similarly, decoctions and infusions made from different Crataegus species were ten times more active than our aqueous extracts [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, a docking study was conducted to investigate potential interactions of rutin with lanosterol 14-α-demethylase ( Figure 12), an enzyme involved in the ergosterol synthesis, in fungi, thus representing a key target of antimycotic therapy [51]. Additionally, plant-derived compounds have long been considered as promising anti-tyrosinase and antimycotic agents [47,48]. According to the bioinformatics analysis (Supplementary Material_Bioinformatics Folder), carvacrol could be responsible of the observed enzyme inhibition against tyrosinase, whereas, according to the fingerprint analysis (Table 2), we hypothesize that carvacrol and rutin could mediate, at least in part, the observed antimycotic activity [49,50].…”
Section: Of 19mentioning
confidence: 99%
“…In our study, total phenolic content in hydroethanolic extract was similar to previously reported data for hydromethanolic (52.60 ± 8.75) and hydroethanolic (48.9 ± 0,3 mg GAE/g dw) extracts of the same species S. raeseri [ 25 , 26 ]. Polar solvents such as water or methanol have been shown to be more efficient than ethyl acetate in extracting total phenolics from S. sipylea , S. perfoliata , S. ozturkii and S. arguta [ 27 , 28 , 29 , 30 ]. However, it should be noted that differences in the extraction method may also affect the content of the components in the extracts.…”
Section: Resultsmentioning
confidence: 99%